Interaction between sulfate-reducing bacteria and aluminum alloys—Corrosion mechanisms of 5052 and Al-Zn-In-Cd aluminum alloys. (1st January 2020) - Guan, Fang; Duan, Jizhou; Zhai, Xiaofan; Wang, Nan; Zhang, Jie; Lu, Dongzhu; Hou, Baorong
Abstract: Microbiologically influenced corrosion caused by sulfate-reducing bacteria (SRB) poses a serious threat to marine engineering facilities. This study focused on the interaction between the corrosion behavior of two aluminum alloys and SRB metabolic activity. SRB growth curve and sulfate variation with and with aluminum were performed to find the effect of two aluminum alloys on SRB metabolic activity. Corrosion of 5052 aluminum alloy and Al-Zn-In-Cd aluminum alloy with and without SRB were performed. The results showed that both the presence of 5052 and Al-Zn-In-Cd aluminum alloy promoted SRB metabolic activity, with the Al-Zn-In-Cd aluminum alloy having a smaller promotion effect compared with 5052 aluminum alloy. The electrochemical results suggested that the corrosion of the Al-Zn-In-Cd aluminum alloy was accelerated substantially by SRB. Moreover, SRB led to the transformation of Al-Zn-In-Cd aluminum alloy corrosion product from Al(OH)3 to Al2 S3 and NaAlO2 .